Bioavailability and anti-inflammatory activity of phenolic acids found in spray-dried nejayote after its in vitro digestion. (December 2017) - Villela-Castrejón, Javier; Antunes-Ricardo, Marilena; Gutiérrez-Uribe, Janet A.
Highlights: Diferulates and triferulates had lower bioavailability than ferulic acid. Anti-inflamatory activity was higher at lower concentration of phenolic acids. Nejayote phytochemicals reduced TNF-α, NO, and NF-κB production. Abstract: The aim of this study was to evaluate in vitro the anti-inflammatory activity of phenolic acids absorbed through a Caco-2 monolayer after simulated digestion of spray-dried nejayote powder. Mouse macrophages (Raw 264.7) were treated with the basolateral fractions obtained at 2, 4, 8, or 12 h from the Caco-2 monolayer permeability experiment to measure the effects on NF-κB, TNF-α, COX-2, interleukin-10 (IL-10), and nitric oxide (NO) levels. When the digested samples were exposed to a Caco-2 monolayer, 67% of total ferulic acid (FA) present in spray-dried nejayote powder was recovered in the basolateral fractions after 8 h. Phenolic acids recovered after 2 h exerted the highest anti-inflammatory activity by inhibiting 53.8%, 93.4%, 86.3% and 84.7% the production of NF-κB, TNF-α, COX-2, and NO, respectively. Future in vivo studies should be designed to reach less than 7 μM of FA and its derivatives to assess the potential health benefits.